Impact of 10% SF6 Gas Compared to 100% Air Tamponade in Descemet's Membrane Endothelial Keratoplasty. (3rd April 2018) - Rickmann, Annekatrin; Szurman, Peter; Jung, Sacha; Boden, Karl Thomas; Wahl, Silke; Haus, Arno; Boden, Katrin; Januschowski, Kai
ABSTRACT: Purpose : To compare the clinical outcomes following Descemet's membrane endothelial keratoplasty (DMEK) with 100% air tamponade versus 10% sulfur hexafluoride (SF6 ) tamponade. Methods : Retrospective analysis of 108 consecutive DMEK cases subdivided by anterior chamber tamponade with 54 eyes receiving 10% SF6 and 54 eyes receiving 100% air injection. A post-hoc matched analysis revealed no statistically significant differences between the groups. The main outcome measurements were the complication rate, including intra- and postoperative complications and graft detachment rate requiring re-bubbling. Clinical outcome included best-corrected visual acuity (BCVA), endothelial cell count (ECC), and central corneal thickness (CCT) measured 1, 3, and 6 months after DMEK surgery. Results : The graft detachment rate with consecutive re-bubbling was 18.5% in the air group and 22.2% in the SF6 group ( p  = 0.2). Remaining small peripheral graft detachments with a clear cornea occurred more often in the 100% air group (air: 22.2%; 12/54, 6/12 inferior compared to SF6 : 7.4%; 4/54, 2/4 inferior; p  = 0.06). The primary graft failure rate was comparable between the two groups. No complete graft detachment occurred. Outcome results for BCVA, ECC, and CCT at all follow-up time points were comparable between the two groups. Conclusion : The clinical outcomes (including re-bubbling rate, primary graft failure rate, and endothelial cell loss) were comparable with 100% air versus 10% SF6 tamponade, whereas other studies suggest that a higher SF6 concentration (20%) may result in a lower re-bubbling rate.